The iron snake. - Hardy, Ronald (New York, Putnam, 1965)
Chronicles the arduous building of a railroad across Uganda at the turn of the century. Emphasizes the toil and expense in the human life and money that culminated in 582 miles of track serving Uganda, Kenya, and Tanganyika.
Bibliography: p. 317-318.
Keywords: Uganda Railway; Uganda Railway